Implementasi Ilmu Keuangan Dan Perilaku Konsumtif Terhadap Pengelolaan Keuangan Pribadi Dan Tanggung Jawab Keuangan Pada Mahasiswa Manajemen Universitas Kristen Indonesia Paulus Makassar - Natalia Panjaya; Manuel A. Todingbua; Claudio Julio Mongan (Jurnal Ekonomi Manajemen dan Bisnis (JEMB), 2026)
This research aims to examine the influence of financial knowledge implementation and consumptive behavior on personal financial management and financial responsibility among management students at Paulus Christian University of Indonesia Makassar. This study is necessary due to the increasing financial challenges faced by students, which are often not accompanied by adequate financial management skills. The research employs a quantitative approach with primary data collected through structured questionnaires distributed to students. The data were analyzed using multiple linear regression analysis to determine both partial and simultaneous effects among variables. Results and discussion: The findings indicate that the implementation of financial knowledge has a positive and significant effect on personal financial management and financial responsibility. Conversely, consumptive behavior has a negative and significant effect on students’ ability to manage finances responsibly. These results highlight the importance of applying financial knowledge in daily financial decision-making. Conclusion: Strengthening financial literacy education and encouraging self-control in consumption behavior are essential to improve students’ financial responsibility and long-term financial well-being.